2017
DOI: 10.3989/scimar.04599.06a
|View full text |Cite
|
Sign up to set email alerts
|

Transport pathways of decapod larvae under intense mesoscale activity in the Canary-African coastal transition zone: implications for population connectivity

Abstract: Summary:We investigate the transport dynamics of decapod larvae in the Canary-African coastal transition zone (C-ACTZ), where larval assemblages are poorly known. In August 1999, during the FAX99 cruise, the waters downstream of the Canary Island archipelago displayed intense mesoscale activity, with numerous cyclonic and anticyclonic eddies as well as upwelling filaments. Our results illustrate a close relationship between these mesoscale oceanographic structures and the distribution of decapod larvae, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
(114 reference statements)
0
11
0
Order By: Relevance
“…This species is one of the most abundant of the mesopelagic community in Canary Island waters (Ariza et at. 2015), although its larval stages have also been collected in September (FAX99 cruise, Landeira et al 2017), and October-November (CANARIAS 9110 cruise, Landeira et al 2009), suggesting a longer spawning season than that observed in the present study.…”
Section: Composition and Larval Assemblagesmentioning
confidence: 38%
See 3 more Smart Citations
“…This species is one of the most abundant of the mesopelagic community in Canary Island waters (Ariza et at. 2015), although its larval stages have also been collected in September (FAX99 cruise, Landeira et al 2017), and October-November (CANARIAS 9110 cruise, Landeira et al 2009), suggesting a longer spawning season than that observed in the present study.…”
Section: Composition and Larval Assemblagesmentioning
confidence: 38%
“…Moreover, C. crangon is an epibenthic shrimp that preferably inhabits soft-sediment in estua-rine habitats (Holthuis 1980) that do not exist in the Canary Islands. It is possible that this larva reached the Gran Canaria coast transported by upwelling filaments from Africa, as has been suggested by Landeira et al (2017), but with the available data it is not possible to support this hypothesis.…”
Section: New Recordsmentioning
confidence: 74%
See 2 more Smart Citations
“…Accurate faunistic analysis of fishery discards may also become an increasing source of biodiversity knowledge that may help to understand biogeographic patterns and dynamic changes in distribution, including early detection of allochtonous and invasive species (Gorelli et al 2016, Anjos et al 2018. Another interesting and necessary activity, which is also carried out in some areas, is the study of meroplanktonic larvae in relation to hydrographic currents and climate change, because it improves knowledge of specific composition and biocenoses, and can explain the presence of new records and the increase of the biogeographical range of some species (Torres 2015, Landeira et al 2017, Landeira and Lozano-Soldevilla 2018. (Holthuis, 1961) 18…”
Section: General Reflections On the Total Specific Richness In The Ibmentioning
confidence: 99%